2017
DOI: 10.1039/c6cp07774a
|View full text |Cite
|
Sign up to set email alerts
|

Model membrane size-dependent amyloidogenesis of Alzheimer's amyloid-β peptides

Abstract: We herein report the mechanism of amyloid formation of amyloid-β (Aβ) peptides on small (SUV) and large unilamellar vesicles (LUVs), which consist of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) lipids. Although Aβ formed fibrils on SUVs at all POPC concentrations used, the lag time, elongation rate, maximum thioflavin T intensity, and fibrillar morphology were distinct, indicating polymorphic amyloid formation. LUVs, at low POPC concentrations, did not markedly affect fibrillation kinetics; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 60 publications
5
34
0
Order By: Relevance
“…As recently demonstrated peptide-based nanodiscs have additional advantages over MSP-nanodiscs [54]. While Aβ interaction with cell membrane accelerates its aggregation [20,38,39], here we show the solvent exposed charged residues in the peptide belt associated with lipids in the nanodisc play a protective role by delaying Aβ40 aggregation (Fig. 5).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…As recently demonstrated peptide-based nanodiscs have additional advantages over MSP-nanodiscs [54]. While Aβ interaction with cell membrane accelerates its aggregation [20,38,39], here we show the solvent exposed charged residues in the peptide belt associated with lipids in the nanodisc play a protective role by delaying Aβ40 aggregation (Fig. 5).…”
Section: Discussionsupporting
confidence: 73%
“…It should also be noted that the presence of small size nanodiscs were found to significantly deaccelerate Aβ40’s aggregation as compared to lipid-free Aβ aggregation. Based on the experimental studies using lipid vesicles, previous studies have shown that Aβ40 aggregation is promoted by very low lipid concentration [20,38,39]. However, as shown in Fig.2c, a very low DMPC concentration in nanodiscs (at 1:1 DMPC:Aβ molar ratio) exhibited a linear correlation between 4F concentration and Aβ40 aggregation (T lag ) kinetics indicating its counter protective role against Aβ40 fibrillation.…”
Section: Resultsmentioning
confidence: 86%
“…Numerous reports over the last decade using reconstituted phospholipid vesicles indicate formation of aggregates along off-fibril forming pathways, paving a way for the generation of structurally-diverse oligomers [107109]. Recently, Aβ42 aggregation on SUV and large unilamellar vesicles (LUV) from POPC lipids showed formation of polymorphic aggregates with distinct biophysical characteristics [110]. In this study, LUVs with high POPC concentrations suppressed amyloid formation that affected fibrillation kinetics, as opposed to those with low POPC concentrations, demonstrating the effect of concentration gradients along the liposome surface in modulating aggregation pathways.…”
Section: Interaction and Modulation Of Aβ Aggregation By Lipidsmentioning
confidence: 99%
“…Recent studies have proposed that solubility and supersaturation are fundamental factors in understanding protein aggregation in solution. [18][19][20][21][22][23][24][25] Proteins over the solubility limit must form insoluble aggregates such as amyloid fibrils from the thermodynamic point of view. However, apparently soluble proteins prior to the phase transition to insoluble solid states are often detected due to kinetic trapping by the metastability of supersaturation, which is certainly linked to the cause and effect relationship with the nucleation and lag time.…”
Section: Hiv Infections Continue To Be a Major Health Issuementioning
confidence: 99%
“…Recent studies have proposed that solubility and supersaturation are fundamental factors in understanding protein aggregation in solution . Proteins over the solubility limit must form insoluble aggregates such as amyloid fibrils from the thermodynamic point of view.…”
Section: Introductionmentioning
confidence: 99%